Pesantren Sebagai Agen Penguatan Ekonomi Islam: Strategi Pemberdayaan Usaha Mikro dengan Prinsip Syariah - Akbar Nuur Purnama Darma Wahana; Muhammad Syaifulloh; Nur Khojin (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
Islamic boarding schools have strategic potential as agents of economic empowerment for the community through the development of micro-enterprises based on sharia principles, especially for post-graduation alumni. With social capital, alumni networks, and the internalization of Islamic values, Islamic boarding schools have the opportunity to become centers of inclusive and sustainable microeconomic transformation. This study aims to analyze the role of Islamic boarding schools in strengthening the Islamic economy and to identify strategies for empowering sharia-based micro-enterprises among Islamic boarding school alumni. This study uses a descriptive qualitative approach with a case study method on alumni from four Islamic boarding schools in Brebes Regency, namely Assalafiyah Luwungragi Islamic Boarding School, Al-Hikmah Benda 1 Islamic Boarding School, Al-Hikmah Benda 2 Islamic Boarding School, and Darunnajat Islamic Boarding School, with a total of 75 respondents. Data collection was conducted through in-depth interviews and analyzed thematically. The results of the study show that most alumni developed micro businesses in the trade, culinary, agriculture, and service sectors based on the sharia values they acquired during their education at Islamic boarding schools. Sharia principles, such as avoiding usury and honesty in transactions, are the main foundations in business management. Entrepreneurship training and alumni networks play a major role in supporting business success, although there are still obstacles in the form of limited access to digital technology, modern markets, and post-graduation business assistance. Therefore, a more structured empowerment strategy is needed, such as the development of Islamic boarding school business incubators, strengthening digital literacy, and partnerships with Islamic financial institutions. This study confirms that Islamic boarding schools have an important role as a model for community-based economic empowerment based on Islamic values and oriented towards the economic sustainability of the community.